Recyclable Iron Oxide Loaded Poly (Methyl Methacrylate) Core/Polyethyleneimine Shell Nanoparticle as Antimicrobial Nanomaterial for Zoonotic Pathogen Controls - Nuttaporn Pimpha (2022)
In this study, a recyclable antimicrobial agent against infectious pathogens in contaminated water was proposed. Iron oxide (IO) loaded poly (methyl methacrylate) (PMMA) core/polyethyleneimine (PEI) shell nanoparticles (PMMA/PEI-IO) was fabricated. The PMMA/PEI-IO showed a cationic surface charge property which is reflected by the protonation behavior of PEI. IO content in PMMA/PEI was evaluated by TGA and indicated that the residue incorporation of IO was 50% by dried weight. The existing of IO in PMMA/PEI was confirmed by the vibrating-sample magnetometer (VSM) showing a superparamagnetic property. The antibacterial ability was confirmed in waterborne bacteria, Escherichia coli and Staphylococcus aureus. The disturbance of the cell membrane integrity occurred after 20 min post-incubation of PMMA/PEI-IO with bacteria. Antimicrobial activity and recycling ability was further confirmed in an infectious, zoonotic and waterborne pathogen, Streptococcus agalactiae. Antiviral activity of PMMA/PEI-IO was observed and proved in an avian flu virus H3N2, a virus that has the potential to contaminate water reservoirs. The result showed that PMMA/PEI-IO nanoparticles were effective in killing H3N2. This study proposes a novel nanoparticle-based antimicrobial agents with recycle ability. Moreover, PMMA/PEI-IO nanoparticle is a potent bactericidal and virucidal agents when tested with waterborn zoonotic pathogens.